2022
DOI: 10.1186/s40168-022-01299-8
|View full text |Cite|
|
Sign up to set email alerts
|

Chicken jejunal microbiota improves growth performance by mitigating intestinal inflammation

Abstract: Background Intestinal inflammation is prevalent in chicken, which results in decreased growth performance and considerable economic losses. Accumulated findings established the close relationship between gut microbiota and chicken growth performance. However, whether gut microbiota impacts chicken growth performance by lessening intestinal inflammation remains elusive. Results Seven-weeks-old male and female chickens with the highest or lowest body… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 82 publications
(86 reference statements)
0
34
0
Order By: Relevance
“…At the genus level, the effect of the two drugs on the structure of the intestinal bacterial community of patients is well-known. Studies have shown that Escherichia – Shigella species can increase endotoxemia, produce endogenous ethanol, trigger strong inflammatory reactions, and cause insulin resistance ( Frost et al, 2021 ; Zhang et al, 2022 ). Megamonas is closely associated with inflammatory bowel disease, colorectal cancer, and obesity ( Chiu et al, 2014 ; Yachida et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…At the genus level, the effect of the two drugs on the structure of the intestinal bacterial community of patients is well-known. Studies have shown that Escherichia – Shigella species can increase endotoxemia, produce endogenous ethanol, trigger strong inflammatory reactions, and cause insulin resistance ( Frost et al, 2021 ; Zhang et al, 2022 ). Megamonas is closely associated with inflammatory bowel disease, colorectal cancer, and obesity ( Chiu et al, 2014 ; Yachida et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Prevotella and Undibacterium are associated with infection and low body weight in chickens ( Falagas and Siakavellas, 2000 ; Zhang, et al, 2022 ). An increase in the abundance of Prevotella and Undibacterium in CHS birds indicates the adverse effect of heat exposure, which was also correlated with a decrease in body weight in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…However, these types of intensive antibiotic-use practices have accelerated the development of antibiotic resistance in bacteria and this has become a major public global health concern (Wang et al, 2019). Therefore, many countries including China have prohibited the use of antibiotics as growth promoters in food animal production and scientists are committed to developing antibiotic alternatives for animal growth promotion (Zhang et al, 2022a). One promising alternative is the use of probiotics or associated metabolites derived from the chicken gut microbiome (Ayalew et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Despite established relationships between gut the microbiota and chicken growth performance, mechanistic details have yet to be formulated. However, intestinal inflammation due to colonization by bacterial pathogens has been linked to poor growth performance and probiotic treatments can counter these effects (Zhang et al, 2022a). Regulation of fat metabolism and improved growth performance have also been directly linked to specific cecal microbiota (Zhang et al, 2022b).…”
Section: Introductionmentioning
confidence: 99%